2018
DOI: 10.21106/ijma.229
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Infant Mortality in Southeast Nigeria: Results from the Healthy Beginning Initiative, 2013-2014

Abstract: Background:Neonatal mortality due to preventable factors occurs at high rates throughout sub-Saharan Africa. Community-based interventions increase opportunities for prenatal screening and access to antenatal care services (ANC) services. The Healthy Beginning Initiative (HBI) provided congregation-based prenatal screening and health counseling for 3,047 women in Enugu State. The purpose of this study was to identify determinants for infant mortality among this cohort.Methods:This was a prospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…For women decision making autonomy, data in 2013 NDHS was collected on the bases of their participation in three dimensions on issues concerning (i) their own health care, (ii) making major household purchases, and (iii) visits to family or relatives without having to take permission 8. For ANC visits, data showed a range of visits from 0 to 36 times during the period of pregnancy with at least 4 visits considered for this study as having attended adequate ANC visits in accordance with WHO standard as at the time of the survey without prejudice to the recent WHO recommendation of a minimum of 8 visits 16,17. In addition, for this study, weights were constructed to correct for imbalance in sampling to ensure national representativeness resulting in a weighted sample of 27,829 women.…”
Section: Methodsmentioning
confidence: 75%
“…For women decision making autonomy, data in 2013 NDHS was collected on the bases of their participation in three dimensions on issues concerning (i) their own health care, (ii) making major household purchases, and (iii) visits to family or relatives without having to take permission 8. For ANC visits, data showed a range of visits from 0 to 36 times during the period of pregnancy with at least 4 visits considered for this study as having attended adequate ANC visits in accordance with WHO standard as at the time of the survey without prejudice to the recent WHO recommendation of a minimum of 8 visits 16,17. In addition, for this study, weights were constructed to correct for imbalance in sampling to ensure national representativeness resulting in a weighted sample of 27,829 women.…”
Section: Methodsmentioning
confidence: 75%
“…Maternal age [ 16 , 17 ], maternal education status [ 18 , 19 ], household wealth status [ 20 ], Antenatal Care (ANC) visit during pregnancy [ 21 , 22 ], parity [ 23 ], birth order [ 24 ], place of delivery [ 25 , 26 ], child nutritional status (stunting, wasting and underweight) [ 26 ], vaccination status [ 27 ], and residence [ 28 ] were reported by previous researchers as significant predictors of infant mortality.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by Samantha Slinkard et al, 2018 who reported lack of access to Antenatal care (ANC) or delayed ANC initiation as an important risk factor for increased IM. 7 According to the 2013 NDHS report, 34% of women did not receive ANC and only 18% of those who received ANC did so in the first trimester. Some factors are associated with this high IMR in Nigeria, such as age of mother, socioeconomic status and region which contribute to the impact of ANC initiation.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors highlighted include place of residence, child's sex, skill of birth attendant, delivery by caesarean operation, birth order, birth interval, maternal education, maternal age, and wealth index. 7 , 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%